(untitled) (ASEAN Engineering Journal, 2024)
A Wireless Sensor Network (WSN) comprises compact, resource-limited devices strategically placed for data collection and transmission, adapting seamlessly across diverse sectors and managing sensitive information. Security is pivotal in these applications, where compromised sensor nodes swiftly jeopardize network integrity, especially without robust security measures. Strategies addressing node compromise center on detecting false data from compromised nodes but often lack precision in tracing the exact source, hindering effective compromised node detection. This paper introduces an inventive anomaly-detection mechanism rooted in trap-based strategies, aiming to prevent sensor node compromise, ensure secure data aggregation, and sustain energy efficiency in WSNs. The trap system integrates deceptive nodes strategically to entice potential attackers, gathering essential attacker details and promptly alerting other network nodes. Consequently, the network excels in identifying attackers and thwarting node compromise, enhancing energy efficiency, network longevity, success rates, and data transmission. Additionally, this approach provides early warning mechanisms for swift attacker detection and attack-type identification, addressing vulnerabilities effectively. By deploying traps proactively, this innovative mechanism not only safeguards against compromises but also fortifies the network's resilience and performance. This proactive strategy aligns with energy efficiency goals in WSNs, elevating the network's security significantly while advancing efficiency across sensitive data domains in sensor network infrastructure.